Namespaces
Variants
Actions

Difference between revisions of "User talk:WikiSysop"

From Encyclopedia of Mathematics
Jump to: navigation, search
Line 6: Line 6:
  
 
===Tests October 27th===
 
===Tests October 27th===
 +
====Case 1====
 
[asy]
 
[asy]
 
draw((0,0)--(3,7),red);
 
draw((0,0)--(3,7),red);
Line 32: Line 33:
 
draw(Label("$A\cap B$",0),g,Arrow);
 
draw(Label("$A\cap B$",0),g,Arrow);
 
</asy>
 
</asy>
 
+
====Case 2====
 
<asy>
 
<asy>
 
size(0,2cm);
 
size(0,2cm);
Line 40: Line 41:
 
label("$Y$",(1,1),NE);
 
label("$Y$",(1,1),NE);
 
label("$Z$",(0,1),NW);
 
label("$Z$",(0,1),NW);
 
+
</asy>  
</asy>   ------------------------------- <asy>
+
====Case 3====
 +
<asy>
 
import three;
 
import three;
 
currentprojection=orthographic(5,4,2,center=true);
 
currentprojection=orthographic(5,4,2,center=true);
Line 53: Line 55:
 
label("(0,0,1)",(0,0,1),Z);
 
label("(0,0,1)",(0,0,1),Z);
 
</asy>
 
</asy>
 
+
====Case 4====
 
<asy>
 
<asy>
 
import three;
 
import three;
Line 68: Line 70:
 
dot(g,red);
 
dot(g,red);
 
</asy>
 
</asy>
 +
====Case 5====
 +
[asy]
 +
pair A,B,C,X,Y,Z;
 +
A = (0,0);
 +
B = (1,0);
 +
C = (0.3,0.8);
 +
draw(A--B--C--A);
 +
X = (B+C)/2;
 +
Y = (A+C)/2;
 +
Z = (A+B)/2;
 +
draw(A--X, red);
 +
draw(B--Y,red);
 +
draw(C--Z,red);[/asy]
  
 
===Previous tests===
 
===Previous tests===

Revision as of 11:25, 27 October 2014

Test Copy&Paste HTML

Test-copy-paste

Test Asymptote

Tests October 27th

Case 1

[asy] draw((0,0)--(3,7),red); dot((0,0)); dot((3,7)); label("Produced with Asymptote "+version.VERSION,point(S),2S); [/asy]

Case 2

Case 3


Case 4

Case 5

[asy] pair A,B,C,X,Y,Z; A = (0,0); B = (1,0); C = (0.3,0.8); draw(A--B--C--A); X = (B+C)/2; Y = (A+C)/2; Z = (A+B)/2; draw(A--X, red); draw(B--Y,red); draw(C--Z,red);[/asy]

Previous tests





Test Cite Extension

Example: Cite-Extension

Test MathJax

\begin{align} \dot{x} & = \sigma(y-x) \\ \dot{y} & = \rho x - y - xz \\ \dot{z} & = -\beta z + xy \end{align}


\[ \frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} = 1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}} {1+\frac{e^{-8\pi}} {1+\ldots} } } } \]


Some Text \( \frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} = 1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}} {1+\frac{e^{-8\pi}} {1+\ldots} } } } \)


Some Text \[ \frac{1}{(\sqrt{\phi \sqrt{5}}-\phi) e^{\frac25 \pi}} = 1+\frac{e^{-2\pi}} {1+\frac{e^{-4\pi}} {1+\frac{e^{-6\pi}} {1+\frac{e^{-8\pi}} {1+\ldots} } } } \]

Pages A-Z

Alphabetically ordered index of all pages

Recent Changes

List of previous changes on EOM

.

How to Cite This Entry:
WikiSysop. Encyclopedia of Mathematics. URL: http://www.encyclopediaofmath.org/index.php?title=WikiSysop&oldid=34091

Test January 12th 2015